Disposable, acetylcholinesterase-coated, screen-printed carbon electrodes for the determination of organophosphorus pesticides. Issue 3 (1st July 2019) - Walter, Piotr; Pepłowski, Andrzej; Górski, Łukasz; Janczak, Daniel; Jakubowska, Małgorzata
Abstract : Purpose: Because of the bioaccumulation effect, organophosphorus pesticides cause long-term damage to mammals, even at small concentrations. The ability to perturb the phospholipid bilayer structure as well as the overstimulation of cholinergic receptors makes them hazardous to humans. Therefore, there is a need for a quick and inexpensive detection of organophosphorus pesticides for agricultural and household use. As organophosphorus pesticides are acetylcholinesterase (AChE) inhibitors, biosensors using this mechanism hold a great promise to meet these requirements with a fraction of reagents and time used for measurement comparing to laboratory methods. This study aims to manufacture AChE-coated, screen-printed carbon electrodes applicable in such amperometric biosensors. Design/methodology/approach: AChE enzyme, known for catalytic activity for the hydrolysis of acetylthiocholine (ATCh), could be used to obtain electrochemically active thiocholine from acetylthiocholine chloride in aqueous solutions. Using Malathion's inhibitory effect towards AChE, pesticides' presence can be detected by reduction of anodic oxidation peaks of thiocholine in cyclic voltammetry. Findings: The conducted research proved that it is possible to detect pesticides using low-cost, simple-to-manufacture screen-printed graphite (GR) electrodes with an enzymatic (AChE) coating. Investigated electrodes displayed significant catalytic activity to the hydrolysis of ATCh. Owing to inhibition effect of the enzyme, amperometric response of the samples decreased in pesticide-spiked solution, allowing determination of organophosphorus pesticides. Originality/value: Printed electronics has grown significantly in recent years as well as research focused on carbon-based nanocomposites. Yet, the utilization of carbon nanocomposites in screen-printed electronics is still considered a novelty in the market. Biosensors have proved useful not only in laboratory conditions but also in home applications, as glucometers are a superior solution for glucose determination for personal use. Although pesticides could be detected accurately using chromatography, spectroscopy, spectrometry or spectrophotometry, the market lacks low-cost, disposable solutions for pesticide detection applicable for household use. With biosensing techniques and electric paths screen-printed with GR or graphene nanocomposites, this preliminary research focuses on meeting these needs.